2011
DOI: 10.1042/bj20101443
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of human adenylate kinases 7 and 8 demonstrates differences in kinetic parameters and structural organization among the family of adenylate kinase isoenzymes

Abstract: Differences in expression profiles, substrate specificities, kinetic properties and subcellular localization among the AK (adenylate kinase) isoenzymes have been shown to be important for maintaining a proper adenine nucleotide composition for many different cell functions. In the present study, human AK7 was characterized and its substrate specificity, kinetic properties and subcellular localization determined. In addition, a novel member of the human AK family, with two functional domains, was identified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 24 publications
(26 reference statements)
2
28
0
Order By: Relevance
“…The AK family comprises nine isozymes that are located in various subcellular compartments and are distributed in tissues as follows: AK1, 5, 7, and 8 are located in the cytosol, AK2, 3, and 4 are located in the mitochondria, and AK6 is located in the nucleus [1], [2], [10][12]. In addition, a recent study using GFP-fusion proteins demonstrated AK9 in both cytosolic and nuclear compartments [13].…”
Section: Introductionmentioning
confidence: 99%
“…The AK family comprises nine isozymes that are located in various subcellular compartments and are distributed in tissues as follows: AK1, 5, 7, and 8 are located in the cytosol, AK2, 3, and 4 are located in the mitochondria, and AK6 is located in the nucleus [1], [2], [10][12]. In addition, a recent study using GFP-fusion proteins demonstrated AK9 in both cytosolic and nuclear compartments [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a lower ratio of p-AMPK/AMPK was detected in the cardiomyocyte nucleus after AK siRNA treatment, which dropped from an average of 3.0 in control to 1.5 in cardiomyocytes isolated from AK1/AK2/AK5-knockdown embryoid bodies. Of note, AK1 knockout mice present no apparent developmental cardiac defects which could be related to overlapping function and compensation provided by complementary adenylate kinase isoforms of which eight are currently known [7], [64]. Deletion of AK2, an isoform silenced here, is embryonically lethal in mice [65] and Drosophila [29] with severe defects in mitochondrial structure and energetics, and human mutations of AK2 are associated with developmental defects [30], [31].…”
Section: Resultsmentioning
confidence: 99%
“…Situs inversus was not detected in Ak7 -/-mice. Ak8 (adenylate kinase 8): 71 All homozygous Ak8 -/-mice in this line developed mild to moderate hydrocephalus, usually restricted to the lateral ventricles (Fig. 13).…”
Section: Ulk4 (Unc-51-like Kinase 4 [C Elegans])mentioning
confidence: 99%
“…It has been postulated that AK7 and AK8 activities may be crucial to meeting the high-energy requirements of motile cilia. 71 Although mice deficient in either AK7 or AK8 each developed hydrocephalus, they differed markedly in disease severity and age of onset. Decreased viability was clearly evident in Ak7 -/-mice, which showed reduced number of homozygotes at time of weaning with very few mutant mice surviving beyond 3 weeks of age.…”
mentioning
confidence: 99%